Are Couples Really Happy after Divorce? An Analysis of the Negative Post-Divorce Effects in Hanif Kureishi’s Short Story Midnight All Day - Güneş, Ali (Journal of History Culture and Art Research, 2016)
This paper examines the negative post-divorce effects on the separated couples in Hanif Kureishi’s short story Midnight All Day. In so doing, it focuses upon two negative aspects related to the post-divorce phases. First, it looks closely at how Kureishi’s fictional male character Ian feels frustrated, unhappy and fragmented in the wake of his divorce from his wife Jane, even though he finds at once a new lover Marina. Secondly, the paper also discusses another disturbing negative aspect of Ian’s life after the break-up with Jane – the negative aspect linked to his parental responsibility towards his daughter. The paper debates that Ian’s the situation is actually almost all the separated couples and their children in the contemporary world. He has a daughter, who stays with her grandmother in London. Whenever he sees a small girl in the street and whenever he thinks of her, he recalls at once his daughter and seems to suffer profoundly from the view that he is unable to fulfil his proper parental responsibility for her and be a good father, a good model for her emotional and social development as in a stable family.